THE INFLUENCE OF LOCUS OF CONTROL AND INDEPENDENCE ON THE PERFORMANCE OF INTERNAL AUDITORS AT THE REGIONAL INSPECTORATE OF BONE BOLANGO REGENCY - Vidya Vanessa Toloh; Sahmin Noholo; Hendra Pratama Danial (Multidisciplinary Indonesian Center Journal (MICJO), 2026)
This study aims to analyze the influence of locus of control and independence on the performance of internal auditors at the Regional Inspectorate of Bone Bolango Regency. This research employs a quantitative approach with a causal research design. The population and sample consist of 38 internal auditors, using a total sampling technique. Data were collected through questionnaires and analyzed using multiple linear regression with the assistance of SPSS software. The results show that partially, locus of control does not have a significant effect on internal auditor performance, while independence has a positive and significant effect. Simultaneously, locus of control and independence significantly influence internal auditor performance. The coefficient of determination indicates that 55.1% of the variation in internal auditor performance can be explained by locus of control and independence, while the remaining 44.9% is influenced by other factors outside the research model. These findings indicate that internal auditor performance is more strongly influenced by professional factors such as independence than by psychological factors such as locus of control. Therefore, efforts to improve internal auditor performance should focus on strengthening auditor independence to ensure objective and professional audit practices.